Socioeconomic development and the impact of natural disasters: some empirical evidences from China - Zhou, Yang; Li, Ning; Wu, Wenxiang; Liu, Haolong; Wang, Li; Liu, Guangxu; Wu, Jidong (Natural Hazards, 2014)
Significant advancements have been made in examining the relationship between economic development and disaster losses at the global and national scales, but very little research has been done at the sub-national level, especially in China. Based on socioeconomic and disaster impact data from 31 provinces (municipalities, and autonomous regions) in China from 1990 to 2010, ordinary least squares regression was used to determine the relationship between socioeconomic development and effects of natural disasters. Results showed that economic development played a distinct role in mitigating disaster damages in the whole China and its eastern, central and western regions. There existed a U-shaped relationship between economic growth and disaster losses in the whole China and its eastern region, and an inverted-U nonlinearity linkage in its central and western areas. These findings further confirmed the existence of a nonlinear relationship between economic development and disaster losses. Economic growth had played a more important role in mitigating disaster losses in the central region of China than that in the western one. Further investigations demonstrated that as economic develops, there were fewer deaths caused by natural hazards in whole China and all its three regions. The combination of the lower level of education, higher unemployment rate and greater gross dependence ratio has contributed to the increase in death toll caused by natural disasters, but this trend could be partly offset by wealth growth.
MAG ID: 2022072748

Social and spatial inequities in exposure to flood risk in Miami, Florida - Chakraborty, Jayajit; Collins, Timothy W.; Montgomery, Marilyn; Grineski, Sara E. (Natural Hazards Review, 2014)
AbstractAlthough environmental justice (EJ) research in the United States has traditionally focused on technological hazards such as air pollution or hazardous waste, the adverse and unequal impacts of Hurricane Katrina have prompted researchers to examine the EJ implications of natural events such as hurricanes and floods. This paper contributes to this emerging literature on EJ and social vulnerability to natural hazards by analyzing racial/ethnic and socioeconomic inequities in the distribution of flood risk exposure in the Miami Metropolitan Statistical Area (MSA), Florida—one of the most hurricane-prone areas in the world and one of the most ethnically and socioeconomically diverse MSAs in the United States. Although previous studies have relied exclusively on the 100-year floodplain to assess the spatial extent of flood exposure, this study makes a systematic distinction between different types of flood zones on the basis of both the probability (100-year versus 500-year versus low/no risk) of flood...
MAG ID: 1991854274